(untitled) (Journal of Global Arts Studies, 2025)
Background： Museums are vital for preserving civilization and providing cultural services. However, homogenization, confused positioning, and lack of systematicity in state-owned museum cultural and creative product development are significant concerns in the cultural sector. Objective： This study systematically analyzes state-owned museum cultural and creative branding’s essential attributes and system construction, then proposes strategies and pathways for building their C&C brand system. This aims to enrich the theoretical framework for such development. Methods: Integrating public cultural services, museology, and brand management theories, this research defines the core logic for state-owned museum brand and C&C development, where cultural undertakings lead cultural industries. It identifies existing problems through a systematic analysis of case studies and practical experiences. Results: The study defines "cultural undertakings guiding cultural industries" as the core logic for state-owned museums and constructs a cultural and creative brand system framework based on public cultural platforms. The framework includes a five-dimensional path of brand value definition, market analysis, product innovation, marketing, and evaluation; establishes an industry-university-research mechanism of "museum-led, social participation, diversified development, and platform-based sales"; and forms a hierarchical brand system, where national museums inherit cultural context, provincial museums showcase diversity, and municipal museums create regional characteristics. Conclusion: Introducing a public cultural service-based system, this study creates a cultural undertaking-led industry paradigm for cultural and creative brands. This innovation addresses homogenization and attribute confusion in state-owned museum cultural and creative development, revitalizing the cultural industry. Through government guidance, museum platform operations, and social collaboration, it secures cultural dissemination and economic benefits, cultivating a distinct Chinese cultural and creative development model and discourse.